2022
DOI: 10.1155/2022/5073944
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cut Off Thickness as Predictor of Endometrial Pathology in Perimenopausal Women with Abnormal Uterine Bleeding: A Cross-Sectional Study

Abstract: Purpose. We aim to determine the predictive value of endometrial thickness by transvaginal ultrasonography (TVS) in diagnosing endometrial pathology and to evaluate whether Doppler complements its diagnostic efficacy in perimenopausal women with abnormal uterine bleeding. Methods. This cross-sectional observational study was conducted among 70 perimenopausal women with AUB who underwent TVS measurement of endometrial thickness (ET) and Doppler flow indices followed by endometrial sampling and histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
2
10
3
Order By: Relevance
“…In the present study, EH/EC was reported at 9.7 (22/254) percent. From previous literatures, prevalence of EH/EC were reported ranging from 4 to 15.7 percent (Sattanakho et al, 2020;Jha et al, 2021;Dhakwa et al, 2021;Soja et al, 2020;Kumari et al, 2022). Our prevalence of EH/EC was within the range of previous works above.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, EH/EC was reported at 9.7 (22/254) percent. From previous literatures, prevalence of EH/EC were reported ranging from 4 to 15.7 percent (Sattanakho et al, 2020;Jha et al, 2021;Dhakwa et al, 2021;Soja et al, 2020;Kumari et al, 2022). Our prevalence of EH/EC was within the range of previous works above.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, this tool may help in differentiating between low-grade and high-grade tumors as well as evaluating the preoperative tumor invasion before surgery [ 11 ]. However, this combination remains controversial among studies [ 12 ]. In Vietnam, this controversy is not of great concern; thus, our study aimed to elucidate the optimal value of ultrasonographic findings and Doppler indices in predicting EC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that an ET >10–11 mm was one of the predictors associated with endometrial malignancy among symptomatic women. 5 9 10 Bivariate cut-off for an ET at 10 mm was chosen in our study, as this value was close to the optimal mathematical value according to logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed no consent regarding the endometrial thickness (ET) cut-off value to be used for the indication of invasive diagnosis in premenopausal symptomatic women. 4 5 Several predictive models based on clinical variables and sonographic predictors have been developed to estimate the individual risk of EC or atypical endometrial hyperplasia (AEH). 6 Nevertheless, most of them focused on perimenopausal and postmenopausal women, and few have been validated.…”
Section: Introductionmentioning
confidence: 99%